Formation of ultralong GaN nanowires up to millimeter length scale and photoconduction study in single nanowire. (September 2017) - Kumar, Mukesh; Kumar, Vikram; Singh, R.
Abstract: Long length GaN nanowire is emerging as desirable requirement for nanodevice applications including sensors, catalytic functionalities and large scale device integration. An alternate approach to obtain ultralong GaN nanowires with length up to millimeter is reported here. High quality ultralong GaN nanowires are obtained from β-Ga2 O3 nanowires. As-formed ultralong GaN nanowires with bandgap of 3.4 eV exhibit wurtzite crystal structure. The high quality of as-formed ultralong GaN nanowires has been confirmed by XRD, Raman, TEM and photoluminescence. The photoconduction in single ultralong GaN nanowire shows high responsivity in order of ~ 10 3 and gains in order of ~ 10 4 . Graphical abstract: